2003
DOI: 10.1016/s0378-1097(03)00426-9
|View full text |Cite
|
Sign up to set email alerts
|

Kakadumycins, novel antibiotics fromStreptomycessp. NRRL 30566, an endophyte ofGrevillea pteridifolia

Abstract: An endophytic streptomycete (NRRL 30566) is described and partially characterized from a fern-leaved grevillea (Grevillea pteridifolia) tree growing in the Northern Territory of Australia. This endophytic streptomycete produces, in culture, novel antibiotics - the kakadumycins. Methods are outlined for the production and chemical characterization of kakadumycin A and related compounds. This antibiotic is structurally related to a quinoxaline antibiotic, echinomycin. Each contains, by virtue of their amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
117
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(119 citation statements)
references
References 9 publications
0
117
0
2
Order By: Relevance
“…Actinobacterial endophytes of terrestrial and marine plants are considered potential sources of novel secondary metabolites (Bascom-Slack et al, 2009;Castillo et al, 2003Castillo et al, , 2007Liu et al, 2014;Strobel et al, 2004). Most of the Streptomyces strains isolated in this study showed antimicrobial activity against a broad range of indicator organisms, which usually cause serious losses in agricultural production.…”
Section: Discussionmentioning
confidence: 89%
“…Actinobacterial endophytes of terrestrial and marine plants are considered potential sources of novel secondary metabolites (Bascom-Slack et al, 2009;Castillo et al, 2003Castillo et al, , 2007Liu et al, 2014;Strobel et al, 2004). Most of the Streptomyces strains isolated in this study showed antimicrobial activity against a broad range of indicator organisms, which usually cause serious losses in agricultural production.…”
Section: Discussionmentioning
confidence: 89%
“…(ATCC 74360), a fungus endophytic in Juniperus communis. 41 The interesting antifungal spectrum exhibited by 66 and its effect on morphology of Aspergillus fumigatus, which was shown to be comparable to that of the glucan synthase inhibitor, pneumocandin B 0 [the natural precursor of the clinical candidate MK-0991 (caspofungin acetate)], has led to an extensive search for other Hormonema isolates from different geographic locations and hosts for enfumafungin (66). Of the 53 isolates screened, antifungal activity was detected in five strains, but by HPLC analysis only two of them were found to produce 66, in amounts similar to the strain ATCC 74360.…”
Section: Metabolites Of Mevalonate Originmentioning
confidence: 99%
“…Streptomyces spp. NRRL 30566 was reported to produced a novel antibiotic, kakadumycins which are DNA intercalating antibiotics that act by inhibiting DNA directed enzymatic RNA synthesis [50]. A novel compound Faeriefungin (polyene macrolides), was isolated from S. griseus, it was reported to have antibacterial, antifungal and insecticidal activities [51].…”
Section: Discussionmentioning
confidence: 99%